Influence of Murabahah and Musyarakah Financing on the Financial Performance of Palopo MSMEs - Nurhikma Nurhikma; Junaidi Junaidi; Sultan Sultan (Perkumpulan Dosen Muda (PDM) Bengkulu, 2026)
Purpose: This study aims to analyze the effect of murabahah and musyarakah financing on the financial performance of Micro, Small, and Medium Enterprises (MSMEs) in Palopo City. Methodology: The research employs a quantitative approach using a survey method by distributing questionnaires to 130 respondents selected through purposive sampling. Data were analyzed using validity and reliability tests, classical assumption tests, and multiple linear regression with SPSS software. Results: The results show that both murabahah and musyarakah financing have a positive and significant effect on MSMEs' financial performance, both partially and simultaneously. Findings: The main findings indicate that musyarakah financing has a more dominant influence compared to murabahah, as its profit-sharing mechanism enhances business efficiency, productivity, and financial stability. Novelty & Originality: The novelty of this study lies in its specific focus on evaluating the effectiveness of two Islamic financing contracts in improving MSMEs' financial performance within a local context, which remains limited in prior research. The originality is strengthened by the integration of empirical analysis based on primary data and the simultaneous testing of both contracts within a single analytical model. Conclusions: In conclusion, optimizing murabahah and musyarakah financing is an effective strategy to improve MSMEs' financial performance, although other external factors also contribute to performance outcomes. Type of Paper: This paper is an empirical research paper.